Association of Systemic Inflammatory Indices with Metabolic Dysfunction–Associated Steatotic Liver Disease and Liver Fibrosis - Wei, Qinghua; Shen, Neng; Chen, Xiang; Cai, Jiacheng (Turkish Journal of Gastroenterology, 2026)
Background/Aims: The newly proposed metabolic dysfunction–associated steatotic liver disease (MASLD) framework reflects the evolving understanding of fatty liver disease, highlighting the importance of exploring novel risk factors beyond traditional metabolic indicators. This study aimed to examine the associations between systemic inflammatory indices and the prevalence of MASLD and liver fibrosis. Materials and Methods: Data from the 2017 MASLD framework reflects the evolving regression was used to assess associations of systemic inflammatory indices—systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), prognostic nutritional index (PNI), aggregate index of systemic inflammation (AISI), inflammation burden index (IBI), neutrophil-to-lymphocyte ratio, neutrophil-to albumin ratio, and pan-immune-inflammation value (PIV)—with MASLD assessed by controlled attenuation parameter (CAP) and liver fibrosis assessed by liver stiffness measurement (LSM), adjusting for confounders. Results: Analysis of CAP and MASLD revealed that elevated SII, SIRI, LMR, IBI, and PNI were significantly associated with higher CAP values, reflecting increased hepatic steatosis, while PLR showed a negative association. Regarding LSM and liver fibrosis, higher SIRI, PNI, IBI, and AISI were significantly associated with increased liver stiffness, whereas PLR remained inversely related. Conclusion: This nationally representative study demonstrates that systemic inflammatory dysregulation is linked to both MASLD and liver fibrosis, with distinct biomarker patterns for steatosis and fibrosis. Cite this article as: Wei Q, Shen N, Chen X, Cai J. Association of systemic inflammatory indices with metabolic dysfunction– associated steatotic liver disease and liver fibrosis. Turk J Gastroenterol. Published online February 12, 2026. doi: 10.5152/tjg.2026.25656.